Hubungan Kesadaran Karyawan tentang Keselamatan, Kesehatan Kerja (K3) dengan Terjadinya Kecelakaan Kerja di Unit Penunjang Rumah Sakit Panti Waluyo Surakarta - Muhammad Alfi Laksana Putra; Nabilatul Fanny; Triyanta Triyanta (STIKes Ibnu Sina Ajibarang, 2025)
Occupational Safety and Health (K3) is an important element in modern hospital management that plays a role in creating a safe and healthy work environment. The type of research used is quantitative with a cross sectional approach. The population and research sample totalled 66 respondents. The sampling technique used was total sampling. The data analysis used was univariate and bivariate analysis analysed using the spearman rank test to see the correlation between the independent variable and the dependent variable. The results of univariate analysis on employee awareness variables regarding K3 show that 64 people (96%) have high awareness, 2 people (4%) have moderate awareness. While the variable work accident 49 people (74%) low work accident, 17 people (26%) moderate work accident. The statistical results of bivariate analysis show that the P-value is 0.007 <0.05 and the correlation value is 0.329. This result states that there is a less strong relationship between employee awareness of OHS and work accidents.